Mechanical Properties of Glass Fibre Reinforced Concrete using Jhama Bricks as Fine Aggregate Replacement (International Journal of Communication Systems and Network Technologies, 2021)
Fibre Reinforced Concrete (FRC) is a composite or a complex material comprising of mixtures of cement, fine aggregates and coarse aggregates and distinct, discontinuous, uniformly dispersed suitable fibres such as natural fibres, artificial fibres, used in civil engineering field and other applications. Fibre is a tiny piece of reinforcing materials holding definite characteristics properties. Fibres may be circular or flat. Conventional concrete has poor tensile strength so its capacity to absorb energy is limited. By strengthening the cement concrete matrix with reinforcing fibrous materials, the weakness in the tension zone can be overcome. Compressive strength, Tensile strength, flexural strength of the materials can improve by usage of fibres in concrete. The concrete is permeable and the porosity is owed to water-void sand air-voids. Due to presence of voids naturally strength of the concrete reduces. The addition of Glass fibres to the cement concrete matrix gradually increases the strength. GFRC is having advantage of being lightweight and thereby the overall cost of construction is reduced, ultimately it brings economy in construction. The addition of Glass fibres and Jhama powder to the cement concrete matrix gradually increases the strength. GFRC is having advantage of being light weight and thereby the overall cost of construction is reduced, ultimately it brings economy in construction. The alternative material can be used as partial or fully replacement of the conventional material. In this research we use the Jhama Brick Dust as an alternative material for the fine aggregate. Here we use the Jhama Brick Dust as partial replacement of the sand from 40% The various tests are carried out such as Compressive, Strength, Flexure Strength and Split Tensile Test at an age of 7 and 28 days of curing. Here the Grade of the concrete is M30 and the mix design is carried out as per IS provision the main purpose of this research is to use the waste material for making the concrete. Here we are using Glass fibre at 0%, 0.5%, 1%, 1.5%, 2% 2.5% and we use the Jhama Brick Dust at 40% as alternative material for fine aggregate.
Keywords: Fibre Reinforced Concrete; Glass Fibre; Jhama Brick; Fine Aggregate Replacement; Compressive Strength; Flexural Strength; Split Tensile Strength